Spatio-temporal evolution of earthquake swarms in the Nordland area of Norway - Igland, Kristoffer (The University of Bergen, 2016)
The double difference earthquake relocation method (DD) is used to improve the seismicity image for regions with high seismic activity. Common location techniques include standard hypocenter location (absolute locations) and the double difference method (relative locations). In this thesis I apply the double difference method of the hypoDD software, on the seismicity in Nordland area Norway. The main aim, is to see if the double difference method, which is known to be more accurate than standard hypocenter location method, provides an improvement on earthquake locations. Which will possible reveal structures with associated orientation. A comparison between absolute locations and relative locations will be conducted using figures, inversion outputs and synthetic test. The double difference method on the seismicity in Nordland was found to be more accurate than standard hypocenter locations. A synthetic test on both real and synthetic data. Shows a reduction in error compared to standard hypocenter location. This indicates that the relocated locations are reliable and robust. The findings of this study in the reveal that the earthquake activity is divided into two parts. The first part is randomly distributed in time and space, and the second part consists of multiple linear alignments of earthquakes trending in NW-SE direction. Further South from the swarm, more linear alignments are trending NW-SE and W-E direction are found. Earthquakes in some sequences are suggested to migrate in time to the South east and dipping towards Northeast and Northwest. Directions of these structures correspond well with previous studies of the area. This indicates that the structures and corresponding seismicity are related to different stress generating mechanisms like ridge push, post-glacial uplift, sediments along the coast and high topography. Master i Geovitenskap MAMN-GEOV GEOV399